The genus Picris (Asteraceae) in southern Italy: contribution to its systematic knowledge - Astuti, Giovanni; Roma-Marzio, Francesco; Peruzzi, Lorenzo (Phytotaxa, 2015)
In southern Italy two species of Picris occur: the widespread P. hieracioides subsp. hieracioides and the endemic P. scaberrima. The latter is still lacking any karyological knowledge, it is imperfectly known as concerns cypselae morphology and its name requires typification. Thus, the name Picris scaberrima is here lectotypified and a map summarizing its distribution is presented. In addition, new data concerning cypselae morphology and karyology of the topotype population of P. scaberrima and of a nearly co-occurring population of P. hieracioides subsp. hieracioides are provided.